The Role of High-Density Lipoproteins in Reducing the Risk of Vascular Diseases, Neurogenerative Disorders, and Cancer. (8th November 2010) - McGrowder, Donovan; Riley, Cliff; Morrison, Errol Y. St. A.; Gordon, Lorenzo
Abstract : High-density lipoprotein (HDL) is one of the major carriers of cholesterol in the blood. It attracts particular attention because, in contrast with other lipoproteins, as many physiological functions of HDL influence the cardiovascular system in favourable ways unless HDL is modified pathologically. The functions of HDL that have recently attracted attention include anti-inflammatory and anti-oxidant activities. High anti-oxidant and anti-inflammatory activities of HDL are associated with protection from cardiovascular disease. Atheroprotective activities, as well as a functional deficiency of HDL, ultimately depend on the protein and lipid composition of HDL. Further, numerous epidemiological studies have shown a protective association between HDL-cholesterol and cognitive impairment. Oxidative stress, including lipid peroxidation, has been shown to be the mediator of the pathologic effects of numerous risk factors of Alzheimer's disease. Lifestyle interventions proven to increase HDL- cholesterol levels including "healthy" diet, regular exercise, weight control, and smoking cessation have also been shown to provide neuro-protective effects. This review will focus on current knowledge of the beneficial effects of HDL-cholesterol as it relates to cardiovascular diseases, breast and lung cancers, non-Hodgkin's lymphoma, as well as its neuroprotective potential in reducing the risk of Alzheimer's disease and dementia.